Selective oxidation of biomass derived 5-hydroxymethylfurfural (HMF) to 2,5-diformylfuran (DFF) over spent dry cell battery cathode material (BCM-2) - Ghadge, Sambhaji S.; Bankar, Shubham R.; Jadhav, Vrushali H. (ACS Applied Engineering Materials, 2024)
Widespread use of batteries across the globe generates a huge amount of waste. This work is the first to report spent dry cell (Zn-Carbon) battery cathode material (BCM-2) as a heterogeneous catalyst for selective synthesis of fine chemical 2,5-diformylfuran (DFF). Cathode material was easily separated from spent batteries, and acid leached followed by calcination to obtain black powder that was denoted as BCM-2. The catalyst was characterized using various techniques such as P-XRD, EDAX, SEM, HR-TEM, TGA, XPS, and BET analysis. Superior catalytic activity was shown by the catalyst for selective formation of DFF using molecular O2 as a sole oxidant. The catalyst was found to give excellent HMF conversion of 97% with 98% high selectivity of DFF. The BCM-2 catalyst was easily recycled and reused without any significant loss in its catalytic activity. This is one of the best examples for a sustainable, cost-effective, and highly efficient catalytic system for the synthesis of the value-added chemical DFF.